KUALITAS TUGAS AKHIR MAHASISWA - Mardiati Busono (Jurnal Kependidikan, 1999)
The average length of srudy of he students of the Dept. of Special Education of the academic year 197/lW used to be 6.12 years and none of the students gradwted with a predicue  cum laude. Research on study obstacles has not yet  "Student  been carried out. Research on Final Task Evalution of the Dept. Of Special Edtrcation of FIP IKIP in 1997' las been geared  ability of the sudentgs of tlat Dept. To do their  toward idewifying obow the finnl ns.ra (thcsis or non-thesis). Based on he results of tlw above mentiorwd research the objective has been to accelerate and to amcliorate the sady, and to improve thc quality  of thertnd task of the srudenu. Thc research appruch is contmt anatysis. Reseorch daa have been obnined  the reports on the  final  task (thesis  and non+hesis of thc academic year 195/j,9% and 195/199V. The dau vatidity of this research is the  justification  of the synchronization of the Ebel formuta.  White the data anatysis is based on the urivariant anatysis. To descibe the ability and the inabiliry of the sndents in pursuing  quatntive ond qmndntive  their  firnl  apprrnch has beenused., The research indicued that 65% of the students had chnsen thesis as their  tasks, and 35vo non-thesis as thcir  firu|  fiom tostcs a tastcs. Most of the proitems were concemed with psychological problcms, and research designs based on surveys elaborated into a.-postfacto antysis. Dau anatysis has been based on non-pramcaic stotistics. Textbools in the bolnsa Indonesia have been 1014 years old, and thc Engrish oncs lave been 20years oa., Thefinaltask of the sndeny courd  be divided iwoTAS (thesis  final  tosks) and rABS (non thesis  firwl tas/.s). For TAS there were 4l subjects and mostty on the btinds (12 subjects or 29,26%). while for TABS there are 23 subjea on menaily hondicapped(7 subjects or i0,43%). There v,as onty one subject on girted children or 4,34%. Ord il v.-s nat athesis, but afirai task (ion-thesis).TIis  due to the gifted fact that there is rw Format Institute which hardle children.To obnin those subjects on gified children be tied at normal schoob and  favoite schools.